The development of the physical element of the crime of rape of a minor in Algerian legislation - Niaf, Amel (Journal of Human Sciences, 2022)
The Algerian legislator succeeded in improving the physical element of raping a minor. The Algerian Penal Code issued under Order 66-156 contained the Penal Code of the crime of raping a minor in Article 336 and was called “indecent assault”. The physical element included extensive acts and then the second paragraph of the text of Article 336 related to the rape of a minor by Order 75-47 supplementing Ordinance 66-156 containing the Penal Code was amended, in which the ’indecent assault’ was preserved. As for the issuance of Law 14-01 supplementing Order 66-156 containing the Penal Code, “indecent assault” was replaced with the term "rape"; thus, amending the physical element by defining the action to became more accurate. Based on the aforementioned, childhood was extended to eighteen years, with the intention of extending the protection.